KIBRA (KIdney/BRAin protein) regulates learning and memory and stabilizes Protein kinase Mζ. (28th October 2013) - Vogt‐Eisele, Angela; Krüger, Carola; Duning, Kerstin; Weber, Daniela; Spoelgen, Robert; Pitzer, Claudia; Plaas, Christian; Eisenhardt, Gisela; Meyer, Annette; Vogt, Gerhard; Krieger, Markus; Handwerker, Eva; et al.
Abstract The WWC1 gene has been genetically associated with human episodic memory performance, and its product KIdney/BRAin protein (KIBRA) has been shown to interact with the atypical protein kinase protein kinase M ζ (PKMζ). Although recently challenged, PKMζ remains a candidate postsynaptic regulator of memory maintenance. Here, we show that PKMζ is subject to rapid proteasomal degradation and that KIBRA is both necessary and sufficient to counteract this process, thus stabilizing the kinase and maintaining its function for a prolonged time. We define the binding sequence on KIBRA, a short amino acid motif near the C‐terminus. Both hippocampal knock‐down of KIBRA in rats and KIBRA knock‐out in mice result in decreased learning and memory performance in spatial memory tasks supporting the notion that KIBRA is a player in episodic memory. Interestingly, decreased memory performance is accompanied by decreased PKMζ protein levels. We speculate that the stabilization of synaptic PKMζ protein levels by KIBRA may be one mechanism by which KIBRA acts in memory maintenance. <boxed-text content-type="graphic" id="jnc12480-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> KIBRA/WWC1 has been genetically associated with human episodic memory. KIBRA has been shown to be post‐synaptically localized, but its function remained obscure. Here, we show that KIBRA shields PKMζ, a kinase previously linked to memory maintenance, from proteasomal degradation via direct interaction. KIBRA levels in the rodent hippocampus correlate closely both to spatial memory performance in rodents and to PKMζ levels. Our findings support a role for KIBRA in memory, and unveil a novel function for this protein.